Effect of the NU-AGE Diet on Cognitive Functioning in Older Adults: A Randomized Controlled Trial - Marseglia, Anna; Xu, Weili; Fratiglioni, Laura; Fabbri, Cristina; Berendsen, Agnes A. M.; Bialecka-Debek, Agata; Jennings, Amy; Gillings, Rachel; Meunier, Nathalie; Caumon, Elodie; Fairweather-Tait, Susan; Pietruszka, Barbara; et al. (Frontiers in Physiology, 2018)
Background: Findings from animal and epidemiological research support the potential neuroprotective benefits from healthy diets. However, to establish diet-neuroprotective causal relations, evidence from dietary intervention studies is needed. NU-AGE is the first multicenter intervention assessing whether a diet targeting health in aging can counteract the age-related physiological changes in different organs, including the brain. In this study, we specifically investigated the effects of NU-AGE's dietary intervention on age-related cognitive decline. Materials and Methods: NU-AGE randomized trial (NCT01754012, clinicaltrials.gov) included 1279 relatively healthy older-adults, aged 65–79 years, from five European centers. Participants were randomly allocated into two groups: “control” (n = 638), following a habitual diet; and, “intervention” (n = 641), given individually tailored dietary advice (NU-AGE diet). Adherence to the NU-AGE diet was measured over follow-up, and categorized into tertiles (low, moderate, high). Cognitive function was ascertained at baseline and at 1-year follow-up with the Consortium to Establish a Registry for Alzheimer's Disease (CERAD)-Neuropsychological Battery and five additional domain-specific single cognitive tests. The raw scores from the CERAD subtests [excluding the Mini-Mental State Examination (MMSE)] and the single tests were standardized into Z-scores. Global cognition (measured with MMSE and CERAD-total score), and five cognitive domains (perceptual speed, executive function, episodic memory, verbal abilities, and constructional praxis) were created. Cognitive changes as a function of the intervention were analyzed with multivariable mixed-effects models. Results: After the 1-year follow-up, 571 (89.1%) controls and 573 (89.8%) from the intervention group participated in the post-intervention assessment. Both control and intervention groups showed improvements in global cognition and in all cognitive domains after 1 year, but differences in cognitive changes between the two groups were not statistically significant. However, participants with higher adherence to the NU-AGE diet showed statistically significant improvements in global cognition [β 0.20 (95%CI 0.004, 0.39), p-value = 0.046] and episodic memory [β 0.15 (95%CI 0.02, 0.28), p-value = 0.025] after 1 year, compared to those adults with lower adherence. Discussion: High adherence to the culturally adapted, individually tailored, NU-AGE diet could slow down age-related cognitive decline, helping to prevent cognitive impairment and dementia.